The distribution of phosphorus, carotenoids and tocochromanols in grains of four Chinese maize (Zea mays L.) varieties. (15th January 2022) - Sun, Xiaohong; Ma, Lei; Lux, Peter E.; Wang, Xuan; Stuetz, Wolfgang; Frank, Jan; Liang, Jianfen
Graphical abstract: Highlights: The distribution of phytochemical in maize kernel differed in genotypes significantly. About 90% of carotenoids were located in the endosperm, while 80% of phosphorous in the germ. Waxy maize contained the highest tocochromanols but the lowest carotenoid. High lysine maize contained the highest levels in carotenoids but lowest tocochromanols. Total carotenoids were negatively correlated with total tocochromanols. Abstract: Grains of three specialty maize varieties and one conventional maize variety cultivated in China were collected and dissected to obtain the germ, endosperm, and pericarp fraction, and the distribution pattern of phosphorus, carotenoids, and tocochromanols was determined. The results showed that phytochemical contents varied significantly among different maize fractions. The germ fraction accounted for 78.3 to 86.5% of the total phosphorus present in the maize kernels. Over 86.9% of carotenoids were located in the endosperm. Except for waxy maize, 64.5 to 74.8% of the tocochromanols were contributed by the germ. Considerable differences in phytochemical contents were observed between the genotypes. Waxy maize contained the highest content of tocopherols, tocotrienols and tocochromanols meanwhile waxy maize had the lowest carotenoid and phytate phosphorus content. High lysine maize contained the highest levels in carotenoids and lowest tocochromanols. Over all, total carotenoids were significantly inversely associated with total tocochromanols.